Low‐dose propranolol regimen for infantile haemangioma. (3rd September 2014) - Tan, Cherise ES; Itinteang, Tinte; Leadbitter, Philip; Marsh, Reginald; Tan, Swee T
<x xml:space="preserve">Abstract</x> Aims Propranolol, now the preferred treatment for problematic proliferating infantile haemangioma (IH), at an empirical cardiovascular dosage of 2–3 mg/kg/day is associated with variable complication rates. A meta‐analysis shows complications in 31% of patients at a mean dosage of 2.12 mg/kg/day. This study reports on the minimal dosage and duration of treatment to achieve accelerated involution and side effects using a stepwise escalation regimen. Methods Consecutive patients with problematic proliferating IH treated with propranolol were identified from our vascular anomalies database. Propranolol was commenced at 0.5 mg/kg/day in two divided doses and increased to 1 mg/kg/day after 24 h. The patients were reviewed after 1 week, and the dosage was increased to 1.5 mg/kg/day. The dosage was further increased by 0.5 mg/kg/day, if necessary, to achieve accelerated involution. Results Forty‐four patients, aged 3 weeks to 11 months (mean, 3.8 months), received propranolol therapy for problematic proliferating IH. The minimal dosage required to achieve accelerated involution was 1.5–2 mg/kg/day. Treatment was maintained for an average of 9.3 months and discontinued at an average age of 14.2 months. Rebound growth occurred in the first patient of this series when propranolol was withdrawn at 7.5 months of age, requiring reinstitution of treatment. Slight rebound growth following cessation of treatment was observed in four other patients, but reinstitution of propranolol was not required. Minor complications were observed in three (6.8%) patients. Conclusions Propranolol at 1.5–2 mg/kg/day, administered in divided doses with stepwise escalation, is safe and effective for treating problematic proliferating IH. Treatment is continued to an average age of 14.2 months.